PersepSi Akuntansi Sektor Publik versus Akuntansi Pemerintahan - Kariyoto, Kariyoto (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
Perceptions that are disseminated in Indonesian government accounting teaching are government accounting substitutes for public sector accounting. The logic of teaching spread always begins from the discussion of clean government and the clean individual. The definition of money in clean government in Indonesia involves the relationship between the executive and the legislature, the consolidated funds and the national loan funds in preparing the appropriate budget plan (RAPBN / RAPBD). The problem is, in general, the public sector is described as a government institution or with a clearer sentence of the ruling government, state government, and national industry of government-owned enterprises, public legal entities, public corporations. But the word is deemed inadequate, so the phrase of the ruling government is still a controversial debate in the context of democracy which states that the people are the most powerful. The purpose of the article explains the correct understanding or perception of public sector accounting. Notwith standing the importance of understanding accounting techniques in governmental organizations, public sector accounting teachings are developed under different conditions.